Kontrol' i upravlenie trenirovochnym processom s pomoshh'ju kompleksa laboratornyh markerov - Manolaki, V. (Science in Olympic Sport, 2020)
Objective. Based on the analysis of the modern literature data, to form an idea of those laboratory markers that can be rationally and reasonably used by the coach during training sessions to control and manage the training process of athletes. Methods. Analysis and generalization of the results of scientifi c and methodological literature and abstract data-bases on the studied issue. Results. Based on literature data analysis and the results of authors` practical work the use of a complex of indices (lactate, urea, glucose content)has been substantiated, changes of which refl ect all metabolic aspects and mechanisms of muscular activity energy supply in the dynamics of training session aimed at development of various physical qualities. Conclusion. Suggested algorithm for the use of laboratory marker complex can be implemented by the coach independently, especially in the presence of portable analyzers. To obtain more detailed data refl ecting the body homeostatic balance status, this complex can be easily supplemented with markers of the enzymatic link (creatine phosphokinase, lactate dehydrogenase, aminotransferase, etc.)as well as the calculation of the muscle tissue damage index.